2002
DOI: 10.1182/blood-2002-01-0316
|View full text |Cite
|
Sign up to set email alerts
|

Oxidized omega-3 fatty acids in fish oil inhibit leukocyte-endothelial interactions through activation of PPARα

Abstract: Omega-3 fatty acids, which are abundant in fish oil, improve the prognosis of several chronic inflammatory diseases although the mechanism for such effects remains unclear. These fatty acids, such as eicosapentaenoic acid (EPA), are highly polyunsaturated and readily undergo oxidation. We show that oxidized, but not native unoxidized, EPA significantly inhibited human neutrophil and monocyte adhesion to endothelial cells in vitro by inhibiting endothelial adhesion receptor expression. In transcriptional coacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
126
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 145 publications
(137 citation statements)
references
References 46 publications
7
126
1
3
Order By: Relevance
“…In our previous studies, we showed that oxidized EPA and not unoxidized EPA pretreatment of HUVEC inhibits leukocyte adhesion to cytokine-stimulated HUVEC, and this effect is mediated through a PPAR␣-dependent pathway. 11,12 In our present studies, we extend these observations and show that oxidized EPA is also effective in inhibiting cytokine-induced endothelial chemokine expression, particularly MCP-1, and propose a mechanism for these antiinflammatory effects.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…In our previous studies, we showed that oxidized EPA and not unoxidized EPA pretreatment of HUVEC inhibits leukocyte adhesion to cytokine-stimulated HUVEC, and this effect is mediated through a PPAR␣-dependent pathway. 11,12 In our present studies, we extend these observations and show that oxidized EPA is also effective in inhibiting cytokine-induced endothelial chemokine expression, particularly MCP-1, and propose a mechanism for these antiinflammatory effects.…”
Section: Discussionsupporting
confidence: 66%
“…In our previous studies, we showed that oxidized EPA and not unoxidized EPA pretreatment of HUVEC inhibits leukocyte adhesion to cytokine-stimulated HUVEC, and this effect is mediated through a PPAR␣-dependent pathway. 11,12 In our present studies, we extend these observations and show that oxidized EPA is also effective in inhibiting cytokine-induced endothelial chemokine expression, particularly MCP-1, and propose a mechanism for these antiinflammatory effects.The fact that oxidation of the omega-3 fatty acids is required for the aforementioned antiinflammatory effects is also pointed out by other studies. Nohe et al and De Caterina et al have shown that prolonged incubation of endothelial cells with native omega-3 fatty acids (26 hours of total exposure, 6 hours before and 20 hours after TNF␣ stimulation) results in inhibition of cytokine and adhesion molecule The nuclear extracts were coincubated with 32 P-labeled NF-B oligonucleotide, and electrophoresis mobility shift assays were performed (nϭ3).…”
supporting
confidence: 66%
See 3 more Smart Citations